2013
DOI: 10.1038/ncomms3504
|View full text |Cite
|
Sign up to set email alerts
|

Roles of dental development and adaptation in rodent evolution

Abstract: In paleontology, many changes affecting morphology, such as tooth shape in mammals, are interpreted as ecological adaptations that reflect important selective events. Despite continuing studies, the identification of the genetic bases and key ecological drivers of specific mammalian dental morphologies remains elusive. Here we focus on the genetic and functional bases of stephanodonty, a pattern characterized by longitudinal crests on molars that arose in parallel during the diversification of murine rodents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 41 publications
2
42
0
Order By: Relevance
“…Including omnivores in this data set represents a challenge since they are expected to fit in none of the diet end‐members, but rather to fall in between. To control this issue, and to test the influence of different environments on feeding habits at an intra‐specific level, two populations of a typical omnivorous murine rodent, the wood mouse ( Apodemus sylvaticus ) were first compared to the data set (Gomes Rodrigues et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…Including omnivores in this data set represents a challenge since they are expected to fit in none of the diet end‐members, but rather to fall in between. To control this issue, and to test the influence of different environments on feeding habits at an intra‐specific level, two populations of a typical omnivorous murine rodent, the wood mouse ( Apodemus sylvaticus ) were first compared to the data set (Gomes Rodrigues et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…Next, because SHH has been shown to inhibit cusp formation by regulating cusp spacing 19,32 , we cultured Eda null samples with a SHH inhibitor, thereby inhibiting the inhibitor. This treatment also circumvents the tendency of EDA to cause the formation of crests or lophs between cusps 10,19,33 , which are found in evolutionarily derived rodents. The experimental results validated the in silico model simulations: inhibition of SHH signalling in cultured Eda null teeth caused the development of more distinct cusps, without eliminating evolutionarily basal features of Eda null teeth such as the height difference between trigonid and talonid (Fig.…”
Section: Retrieving Ancestral Character Statesmentioning
confidence: 99%
“…By varying the concentrations of paracrine factors involved in cusp formation, the authors were able to reconstitute the formation of the trigonid cusp (the first part of the molar to have evolved), and by further changing these concentrations, they brought forth the talonid cusp, which evolved more recently and is used for shearing food. This account, enabled by mathematical approaches (Kavanagh et al 2007; Salazar-Ciudad and Jernvall 2010) and integrated into paleo-ecological models (Rodrigues et al 2013;Luo 2014), demonstrated "how combining development and function can help to evaluate adaptive scenarios in the evolution of new morphologies" (Rodrigues et al 2013).…”
Section: Paleontologymentioning
confidence: 99%